Distant Pituitary Adenoma Spread: A Systematic Review and Report of 2 Cases. Issue 3 (March 2022) - Azizkhanian, Ida; El Ahmadieh, Tarek Y.; Palmisciano, Paolo; Abou-Mrad, Zaki; Daoud, Elena V.; Essibayi, Muhammed Amir; Connors, Scott; Aoun, Salah G.; Kim, Jun; Hatanpaa, Kimmo J.; Garzon-Muvdi, Tomas; Barnett, Samuel L.; et al.
Abstract : BACKGROUND: Distant spread of pituitary adenoma outside the sellar/suprasellar region is classified as pituitary carcinoma. Cerebrospinal fluid (CSF)–born spread of pituitary adenoma can occur after tumor cell spillage into the CSF space after surgery, irradiation, or apoplexy and is not necessarily related to intrinsic tumor biology. OBJECTIVE: To systematically review the literature and describe the clinical characteristics and treatment strategies of patients with pituitary carcinomas. We further present 2 cases from our institution. METHODS: A single-center retrospective review of patients with pituitary adenoma spread to distant intracranial locations between 2000 and 2020 was performed. Electronic databases were searched from their inception to May 25, 2021, and studies describing patients with pituitary spread to distant locations were included. RESULTS: Of 1210 pituitary adenoma cases reviewed, 2 (0.16%) showed tumor spread to distant locations. We found 134 additional cases (from 108 published articles) resulting in a total of 136 cases (61.9% were male). The time to tumor spread ranged between 0 and 516 months (median: 96 months). The follow-up duration ranged between 0 and 240 months (median: 11.5 months). All but 2 patients (98.5%) underwent surgical resection before adenoma spread. The 2 exceptions included a patient with evidence of an apoplectic event on autopsy and another patient with leptomeningeal pituitary spread but an unclear history of apoplexy. Elevated tumor markers were not linked to poor outcomes. CONCLUSION: Distant spread of pituitary adenoma may occur after surgery, irradiation, or apoplexy. It is not necessarily associated with a malignant clinical course.